Massage as a Mechanotherapy for Skeletal Muscle. Issue 2 (April 2021) - Van Pelt, Douglas W.; Lawrence, Marcus M.; Miller, Benjamin F.; Butterfield, Timothy A.; Dupont-Versteegden, Esther E.
Abstract : Massage is anecdotally associated with many health benefits, but physiological and clinically relevant mechanisms recently have begun to be investigated in a controlled manner. Herein, we describe research supporting our hypothesis that massage can be used as a mechanotherapy imparting biologically relevant adaptations in skeletal muscle and improving muscle properties. Abstract : Massage is a mechanotherapy that promotes recovery of skeletal muscle after damaging exercise and disuse atrophy.